Biochemical Action of Vaccines in Iraqi Patients with COVID-19 Infection (Baghdad Science Journal, 2023)
The aim of the present study is to compare the biochemical action of the three vaccines taken in Iraq: Pfizer Biontech, AstraZeneca Oxford and Sinopharm based on biochemical parameters. Seventy COVID-19 Iraqi patients ( males and females ) were participated in the present study and classified into 7 groups : Gc :  COVID-19 patients ( without vaccine ) , Gp1: COVID-19 patients took one dose of Pfizer Biontech, Gp2 : COVID-19 patients took two doses of Pfizer Biontech, Ga1 : patients took one dose of AstraZeneca Oxford vaccine , Ga2: patients took two doses of AstraZeneca Oxford vaccine , Gs1 : patients took one dose of Sinopharm vaccine and Gs2: patients took two doses of Sinopharm vaccine. Patients were compared with healthy subjects (without vaccine) as a control group (Gh). The D-dimer level was highly significantly increased in Gc compared with Gh and was highly significantly decreased in Gp1 , Ga1 , Ga2 , significantly decreased in Gp2 and non-significantly decreased in Gs1 and highly significant increased in Gs2 compared with Gc. CRP level was significantly increased in Gc compared with Gh while it was significantly decreased in Gp1, Gp2, Ga1 , Ga2 , Gs1 , Gs2 compared with Gc. IgG and IgM levels were increased in Gc but decreased after taking vaccines ( except Ga2 for IgG and Gp2 for IgM )   The present study submits a novelty to the field of COVID-19 by highlighting the chemical aspects of vaccines used in Iraq